Algorithms, sequential & parallel a unified approach - Miller, Russ; Boxer, Laurence (Prentice Hall, 2000)
This work aims to provide an understanding of the analysis and applications of algorithimic paradigms, to both the traditional sequential model of computing and to a variety of parallel models. Concepts are applied to a broad range of subject areas, including matrix operations.